KEBIJAKAN PENANGGULANGAN KEMISKINAN DI KABUPATEN KULON PROGO, REALISASI JANJI KAMPANYE BUPATI HASTO WARDOYO DI TAHUN PERTAMA PEMERINTAHAN PERIODE KE DUA - Harjanta, SL. (Jurnal Manajemen Publik dan Kebijakan Publik (JMPKP), 2020)
This study examines the realization of the promise of the Kulon Progo regional leader pair Hasto Wardoyo-Sutedjo. During the 2017 election campaign, the incumbent couple was quite prominent in campaigning for the success of the poverty alleviation program. The success of the poverty program during the previous administration, finally succeeded in delivering Hasto-Tedjo to maintain the seat of regent and vice regent of Kulon Progo. Specifically, this research focuses on how to implement a home surgery program. Home renovation is one of the salient poverty reduction programs carried out by Regent Hasto Wardoyo. This program is quite popular because there are still many Kulon Progo residents who inhabit unfit homes. Another interesting thing is that the funding of this program does not rely on the APBDes, APBD or APBN. However, sourced from private companies and BUMD CSR. In addition, the house renovation program is also funded by the zakat of civil servants managed by Bazda Kulon Progo. Despite having made a number of anti-poverty programs, the number of poor people in Kulon Progo is still quite high. Based on BPS data for 2017, the poverty rate is 21 percent. This poverty rate is still relatively high. Compared to the previous year, the poverty rate only fell around 0.3 percent